Rivaroxaban does not increase hemorrhage after thrombolysis in experimental ischemic stroke - Ploen, Robert; Sun, Li; Zhou, Wei; Heitmeier, Stefan; Zorn, Markus; Jenetzky, Ekkehart; Veltkamp, Roland (Journal of cerebral blood flow & metabolism, 2014)
The management of acute ischemic stroke during anticoagulation with a novel oral anticoagulant (NOAC) is challenging because intravenous thrombolysis is contrai...
Published: December 18, 2013
Gesehen am 16.09.2020